2016
DOI: 10.17795/semj39038
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes and Practices of Internal Medicine Residents Towards Deep Vein Thrombosis Prophylaxis in a University Hospital in Tehran

Abstract: Background: Deep Vein Thrombosis (DVT) is a major problem in hospitalized patients. There is discrepancy between healthcare providers' knowledge and their clinical practice regarding DVT prophylaxis. In this study we aimed to evaluate knowledge, attitude and practices of internal medicine residents at an educational hospital in Tehran. Methods:This cross-sectional study was conducted during December 2015 at Shariati hospital of Tehran, IRAN. A questionnaire covering five domains of clinical scenarios, adherenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
0
1
Order By: Relevance
“…The results reported that nurses had a poor level of VTE practices. This finding does not align with studies conducted among medical staff that showed good practice towards VTE prophylaxis (Ebrahimpur et al, 2016;Zobeiri & Najafi, 2011). Poor practices may result from poor financial rewards, supervision, and a lack of training programs and standardized protocols (Rababa et al, 2022).…”
Section: Discussioncontrasting
confidence: 58%
“…The results reported that nurses had a poor level of VTE practices. This finding does not align with studies conducted among medical staff that showed good practice towards VTE prophylaxis (Ebrahimpur et al, 2016;Zobeiri & Najafi, 2011). Poor practices may result from poor financial rewards, supervision, and a lack of training programs and standardized protocols (Rababa et al, 2022).…”
Section: Discussioncontrasting
confidence: 58%